1974
DOI: 10.1182/blood.v44.6.837.837
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia in Shoe-Workers Exposed Chronically to Benzene

Abstract: From 1967 to September 1973, 26 patients with acute leukemia or preleukemia were seen in Istanbul among 28,500 shoeworkers exposed chronically to benzene. The incidence of leukemia among these workers was 13/100,000, which is a marked and statistically significant increase over that for leukemia in the general population and provides cogent evidence for the clinical impression of a leukemogenic effect of benzene in man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1
1

Year Published

1977
1977
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(47 citation statements)
references
References 7 publications
3
42
1
1
Order By: Relevance
“…Up to 1974, some case reports or patient series were published in the medical literature, but these reports depended only on clinical findings and not on an epidemiological method. A Turkish haematologist, Pofessor Muzaffer Aksoy conducted an epidemiologic study and reported his findings clearly showing a relationship between benzene and leukemia, in 1974 5) .…”
Section: Occupational Health / Safety In the Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 1974, some case reports or patient series were published in the medical literature, but these reports depended only on clinical findings and not on an epidemiological method. A Turkish haematologist, Pofessor Muzaffer Aksoy conducted an epidemiologic study and reported his findings clearly showing a relationship between benzene and leukemia, in 1974 5) .…”
Section: Occupational Health / Safety In the Worldmentioning
confidence: 99%
“…According to the evidence of carcinogenicity in humans, the occupational agents are categorized into four groups: i) sufficient evidence, ii) limited evidence, iii) insufficient evidence and iv) lack of evidence of carcinogenicity in humans. Occupational exposure to benzene and its carcinogenicity in humans is wellestablished [1][2][3][4]5) .…”
mentioning
confidence: 99%
“…The association between leukemia and benzene has been described among workers exposed to benzene in several productive sectors. The International Agency of Research on Cancer classified benzene as carcinogenic to humans on the basis of case series reported in workers exposed to high levels of benzene in shoe manufacturing and printing in Italy, France, and Turkey as well as some epidemiologic studies of workers in shoe production and the rubber industry [Aksoy et al, 1974;Infante et al, 1977;Rinsky et al, 1981;IARC, 1982]. Subsequently, new data from cohort studies have confirmed a strong association between leukemia and benzene exposure [Rinsky et al, 1987;Crump, 1994Crump, , 1996Paxton et al, 1994a,b;Seniori Costantini et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…(2) 300 ppm, 2 weeks (c) (1) 100 ppm, 8 days, [Li, 1992] a Body weight: upto100 mg/kg/day,12 months or2 years, (oral) in rats [NTP, 1986] Cellularity (spleen) T-cell: at 31ppm, 6 days, and at 300 ppm, 2^5 weeks, (inhalation) in mice [Rozen et al, 1984] Cellularity (bone marrow): at 25 ppm, 2 weeks Cellularity B,Tand Tcell subset (spleen): at100 ppm, 20 days (inhalation) in mice [Rosenthal and Snyder, 1987] Cellularity B lymphocytes (bone marrow): at10 ppm, 6 days, (inhalation) in mice [Rozen et al,1984] Cellularity (bone marrow) at 25 ppm, 2 weeks (inhalation) in mice [Cronkite et al, 1985] Cellularity ( Wells and Nerland [1991] (2) Klan et al [1990] (b) Aoyama [1986] (c) Aksoy et al [1987] a (d) Aksoy et al [1971Aksoy et al [ , 1972Aksoy et al [ ,1974 Mitogenic response (T-cell) lymphocyte to PHA (peripheral blood): (occupational) humans [Yardley-Jones et al,1988] PFC to SRBC: at 400 ppm, 2 or 4 weeks (inhalation) in rats Host resistance s. zooepidemicus: at10 ppm, 1or 5 days (inhalation in mice) [Aranyi et al, 1989] (a Rozen and Snyder [1985] (c) Hsieh et al [1990] Surface markers:…”
Section: Resultsmentioning
confidence: 99%